Metabolomics Study of Whole-body Vibration on Lipid Metabolism of Skeletal Muscle in Aging Mice - Jiang, Dingwen; Liu, Chang; Chen, Ye; Xing, Xuejiao; Zheng, Danmeng; Guo, Zhanpeng; Lin, Sen (International Journal of Sports Medicine, 2020)
Ageing increases the occurrence and development of many diseases. Exercise is believed to be an effective way to improve ageing and skeletal muscle atrophy. However, many elderly people are unable to engage in active exercise. Whole-body vibration is a passive way of moving that is especially suitable for the elderly and people who find it inconvenient to exercise. Metabolomics is the systematic study of metabolic changes in small molecules. In this study, metabolomics studies were performed to investigate the regulatory effect of whole-body vibration on the skeletal muscles of ageing mice. After 12 weeks, we found that whole-body vibration had the most obvious effect on lipid metabolism pathways (such as linoleic acid, α-linolenic acid metabolism, glycerophospholipid metabolism pathways) in skeletal muscle of ageing mice. Through further research we found that whole-body vibration decreased the levels of triglycerides, total cholesterol, low-density lipoprotein cholesterol and very low-density lipoprotein in blood; decreased the lipid deposition in skeletal muscle; decreased the protein expression of monocyte chemoattractant protein-1 and interleukin-6; improved the protein levels of phosphorylated insulin receptor substrate-1, phosphate phosphoinositide 3-kinase and p-AKT; improved the protein levels of klotho; and decreased the protein expression of p53. These findings reveal that whole-body vibration might postpone senility by attenuating lipid deposition and reducing chronic inflammation and the insulin resistance of skeletal muscle.
Keywords: metabolomics; aging; whole body vibration; skeletal muscle; insulin resistance